UJI DAYA HASIL SEMANGKA HIBRIDA (F1) DARI SELEKSI GALUR MURNI - Anung Wahyudi; Rizki Apri Danil; Ria Putri; Akbar Hidayatullah Zaini; Septiana Septiana (Jurnal Agrotek Tropika, 2024)
Pure line selection is carried out in watermelon plant breeding programs to produce hybrid varieties with certain advantages and uniqueness that are different from other watermelon varieties. The aim of the research was to test the yield of F1 hybrid watermelon resulting from a selection of pure line parental crosses on lowland land (Seed Teaching Farm-Lampung). The research used six selected hybrid watermelon genotypes and four hybrid (commercial) variety genotypes as comparison varieties. The experimental design used was a Randomized Block Design (RAK) with further testing using Duncan's multiple range test at the 5% level. The research results showed that the WM 2210-0616 genotype had the highest production yield, namely 17.14 t.ha-1 compared to other genotypes. Watermelon genotypes that have the potential to be registered as new superior varieties include WM 2210-0616; WM 2210-1011; WM 2210-0608; and WM 2210-0401. These four genotypes have advantages in fruit weight, skin color, fruit shape, sugar content, and resistance to breaking during transportation. These advantages are attractive to consumers in developing hybrid varieties in the lowlands area.